KOMITMEN ORGANISASI, MODEL KEPEMIMPINAN MANAJERIAL DAN PENGARUHNYA TERHADAP KINERJA - Kristianto, Djoko (Universitas Slamet Riyadi, 2009)
Abstract The make-up of officer performance influenced by various factor both for coming from itself officer and also coming from institution environment. Factors coming in officer self among others organizational commitment. While factor from outside can be in the form of the managerial performance. Organizational commitment have the influence to officer performance. Commitment employees of institution can be made one of the guarantees to take care of the continuity of institution. A leader claimed have to have the ability lead and intellectual ability is which no doubt so that in deciding policy well accepted in organization led. With the existence of adequate leadership managerial, hence officer will have the good perception so that all his action will be made by peer or its example subordinate in working. Keywords: organizational commitment, managerial performance, leadership